2015
DOI: 10.1080/14759551.2015.1062012
|View full text |Cite
|
Sign up to set email alerts
|

Caste, purity, and female dress in IT India: Embodied norm violation as reflexive ethnographic practice

Abstract: This article proposes the methodology of embodied norm violation for overcoming the dichotomy between cognitive reflexivity and embodied ethnographic practice. The methodology is derived from the author's own embodied experiences as a female Indo-German ethnographer in the field of IT India. For exemplifying the methodology and its potential, this article focusses on two field-related phenomena, namely adhering to a vegetarian diet and dressing the female body. It uses them to gather insights on embodied purit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Institute of Technology Chennai), while others (e.g., Indian Institute of Science Bangalore) dedicated a cafeteria to serve only vegetarian food, which came to be seen as an exclusive dining area for Brahmins, even though other cafeterias served both vegetarian and 'nonvegetarian' food (Thomas, 2020). Notably, individuals from lower castes often adopt vegetarianism after being promoted to managerial positions (Mahadevan, 2015).…”
Section: Caste As An Institution That Affects Workplacesmentioning
confidence: 99%
“…Institute of Technology Chennai), while others (e.g., Indian Institute of Science Bangalore) dedicated a cafeteria to serve only vegetarian food, which came to be seen as an exclusive dining area for Brahmins, even though other cafeterias served both vegetarian and 'nonvegetarian' food (Thomas, 2020). Notably, individuals from lower castes often adopt vegetarianism after being promoted to managerial positions (Mahadevan, 2015).…”
Section: Caste As An Institution That Affects Workplacesmentioning
confidence: 99%
“…The third wave of IHRM research includes new themes -postcolonial analysis (Boussebaa and Morgan, 2014;Mahadevan, 2015) and gender discrimination in foreign assignments (Adler, 1984(Adler, , 1987Altman and Shorthand, 2001;Janssens et al, 2006;Mayrhofer and Scullion, 2002;Metcalfe, 2006;Tung, 2004) -while the dominance of positivism is inevitable and can be identified in perhaps the most influential textbook in the field, that of Dowling et al (1999). There is a growing number of publications in cross-cultural management, which intentionally apply critical approaches (Mahadevan et al, 2020;Primecz et al, 2016;Romani et al, 2018bRomani et al, , 2020, and these studies can inspire further critical IHRM studies in the future.…”
Section: Theoretical Foundations Of the Reviewmentioning
confidence: 99%
“…The findings clearly demonstrated that for Muslim women managers, the decision to adopt veiling seems to have been very personal, even if there was some family pressure or social expectations in their surroundings to adopt veiling. Similar pressures are not applied to men, as has been observed in other cultures, such as India (Mahadevan, 2015). Nevertheless, the change was not simply incidental, and sociocultural-religious messages played a decisive part in women's decisions (Bhimji, 2009;Droogsma, 2007;Prasad, 2012).…”
Section: Discussionmentioning
confidence: 81%
“…A few Muslim female school principals chose to resist these pressures and were very dissatisfied by this phenomenon. Yet, they also noted the advantages of adopting traditional clothing as principal of a Muslim school (Mahadevan, 2015).…”
Section: Veiling Is Part Of Our Tradition and Religious Faithmentioning
confidence: 99%